The Law of the Sea Convention : US accession and globalization - Nordquist, Myron H.; Moore, John Norton, 1937-; Soons, Alfred H. A.; Kim, Hak-so (Center for Oceans Law and Policy (Series), 2012)
The Law of the Sea Convention: US Accession and Globalization, provides valuable insight into a number of contemporary and pressing issues concerning the world's oceans and their management . Brought together at the 34th Annual Conference of the Center for Oceans Law and Policy, University of Virginia School of Law (COLP), Part l reports on the work of international experts which considers the impact of the lack of US participation in UNCLOS, evaluating topics such as energy and economic development as well as ramifications for U.S. national security and navigational rights. The second secti.